2021
DOI: 10.1039/d1mh00461a
|View full text |Cite
|
Sign up to set email alerts
|

A highly transparent ionogel with strength enhancement ability for robust bonding in an aquatic environment

Abstract: The underwater adhesive with strong, fast and stable adhesion ability has become an urgent requirement for various industrial applications. Herein, a highly transparent ionogel based on fluorine-rich poly(ionic liquid) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 42 publications
2
86
0
Order By: Relevance
“…3 Existing challenges include the destruction of the hydration layer, the contradiction between the excellent interface adaptability and tough mechanical strength of the hydrogel, and the decrease in adhesion capacity over time dominated by the high swelling properties of the hydrogel. 4,5 Several strategies have been developed to eliminate the barriers of the hydration layer on the surface of the adhesive matrix, such as the construction of chemical bonding between the surface of the hydrogel and the substrate, 6 introducing hydrophobic groups into the hydrogel, 7,8 and rapidly absorbing interfacial water through the dry polymer network of the hydrogel. 9 In order to take advantage of the interface adaptability and the mechanical property for superior persistent adhesion capability, hydrogels with loose polymer chains are usually first applied, and then a denser polymer network is formed by exposure to external environmental stimuli (e.g., UV light, 4 temperature 10 and water molecules 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Existing challenges include the destruction of the hydration layer, the contradiction between the excellent interface adaptability and tough mechanical strength of the hydrogel, and the decrease in adhesion capacity over time dominated by the high swelling properties of the hydrogel. 4,5 Several strategies have been developed to eliminate the barriers of the hydration layer on the surface of the adhesive matrix, such as the construction of chemical bonding between the surface of the hydrogel and the substrate, 6 introducing hydrophobic groups into the hydrogel, 7,8 and rapidly absorbing interfacial water through the dry polymer network of the hydrogel. 9 In order to take advantage of the interface adaptability and the mechanical property for superior persistent adhesion capability, hydrogels with loose polymer chains are usually first applied, and then a denser polymer network is formed by exposure to external environmental stimuli (e.g., UV light, 4 temperature 10 and water molecules 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Several strategies have been developed to eliminate the barriers of the hydration layer on the surface of the adhesive matrix, such as the construction of chemical bonding between the surface of the hydrogel and the substrate, 6 introducing hydrophobic groups into the hydrogel, 7,8 and rapidly absorbing interfacial water through the dry polymer network of the hydrogel. 9 In order to take advantage of the interface adaptability and the mechanical property for superior persistent adhesion capability, hydrogels with loose polymer chains are usually first applied, and then a denser polymer network is formed by exposure to external environmental stimuli (e.g., UV light, 4 temperature 10 and water molecules 11 ). Nevertheless, the construction and application of hydrogel adhesives that can simultaneously address the abovementioned challenges to achieve robust and persistent adhesion in physiological environments are still rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…
applications, including solid electrolytes, [7] energy storage/generation devices, [8][9][10] electroactive actuators, [11] strain sensors, [12,13] soft robotics, [14] stretchable touch panels, [15] membrane separation, [16] and so on.To further expand the applications of ionogels, different strategies have been reported to combine various other desirable properties with ionogels, including self-healing capability, [17][18][19] high mechanical strength and resilience, [20,21] resistance against water and organic solvents, [22,23] and self-adhesiveness. [12,24] The integration of different properties with the highly conductive and stable nature of ionogels is essential to meet the requirements for practical applications in complex scenarios. For example, very recently, Wu et al reported a class of ionogels with underwater self-healing ability and underwater adhesiveness, which demonstrated intriguing applications such as underwater communication.
…”
mentioning
confidence: 99%
“…To further expand the applications of ionogels, different strategies have been reported to combine various other desirable properties with ionogels, including self-healing capability, [17][18][19] high mechanical strength and resilience, [20,21] resistance against water and organic solvents, [22,23] and self-adhesiveness. [12,24] The integration of different properties with the highly conductive and stable nature of ionogels is essential to meet the requirements for practical applications in complex scenarios. For example, very recently, Wu et al reported a class of ionogels with underwater self-healing ability and underwater adhesiveness, which demonstrated intriguing applications such as underwater communication.…”
mentioning
confidence: 99%
“…Owing to the introduction of [EMIM][Ac], the RIG demonstrated a large amount of exposed bondable sites on its surface. It can bond with different adherends through diverse supramolecular interactions, including hydrogen bonds, electrostatic, ion-dipole, coordination, and hydrophobic interactions [38][39][40][41] (Figure 3a). In detail, for the hydrophilic substrates surface, the hydrogen bonds, electrostatic, and coordination may account for the stable interaction.…”
Section: Dynamically Stable Cooling Interfaces Of Rig Assisted By Str...mentioning
confidence: 99%